Myotonic dystrophy type 1 and pseudo-obstruction in a child with smooth muscle α-actin deficiency and eosinophilic myenteric plexitis - Pelizzo, Gloria; Calcaterra, Valeria; Villanacci, Vincenzo; Mura, Giovanni Battista; Bassotti, Gabrio (Turkish Journal of Gastroenterology, 2018)
Abstract Myotonic dystrophy (MD) frequently involves the gastrointestinal tract, where it can manifest as chronic intestinal pseudo-obstruction (CIPO), particularly in adults. This manifestation is quite uncommon in children. We report the case of a 12-year-old boy with MD type 1 and CIPO, in which a pathologic assessment revealed an association with smooth muscle α-actin deficiency in the external muscular layer of the ileum, and with features of eosinophilic plexitis and eosinophilic muscle infiltration in the colon. In this peculiar case, the clinical aspects of CIPO might have been due to the involvement of several neuromuscular mechanisms. Cite this article as: Pelizzo G, Calcaterra V, Villanacci V, Mura GB, Bassotti G. Myotonic dystrophy type 1 and pseudo-obstruction in a child with smooth muscle α-actin deficiency and eosinophilic myenteric plexitis. Turk J Gastroenterol 2018; 29: 226-9.